CONSIDERATIONS ON THE SELECTIVE MAINTENANCE MODEL FOR THE COMPLEX SYSTEMS - Gheorghe NEGRU (Fiabilitate şi Durabilitate)
The paper presents the mathematical model of the selective maintenance as well as a numerical application of the method in the case of the remote control systems.